PERANAN DALANG WAYANG KULIT DALAM PROPAGANDA PEMBANGUNAN DI BAWAH ORDE BARU - Fadhil Nugroho Adi (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2017)
This research looks at the process of delivering propaganda by the dalangs (puppeteers) in Wayang Kulit performances in Central Java in 1986-1998. Using mass communication approach and theories, this research has revealed that the dalangs were co-opted by the government when they deliver the New Order Government's messages to their audience. The Government's strong efforts to cast its political propaganda through the dalangs were so obvious after the 30th September Movement. As a result, there were changes in the concepts of wayang kulit performance. The dalangs very often delivered the Government messages both implisitly or explicitly. These messages are delivered through janturan (narration), ginem (dialogue), gending (music), limbukan (interlude scene between a mother and her daughter), and gara-gara (clown scene). However, this condition hadencouraged the dalangs' creativity to compose new stories, modify stories, and compose songs which tell about national development.